2020
DOI: 10.1590/1678-4324-2020200178
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Chitosan Addition in Whey-based Biodegradable Films

Abstract: Whey, a by-product of dairy industry, is a feedstock widely employed in the production of biodegradable films. However, these films present some limitations when considering the performance of synthetic polymers, especially biological transformation by decomposition. This work aimed to evaluate the effects of chitosan addition to whey-based films to improve films physical-chemical properties and resistance to microbial degradation. The results showed that there was an interaction effect between the chitosan co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Figure 12a shows the synthesis of film C from the mixture of 0.1 g (ZnO/CuO nanoparticles), 10 mL (PVA 2.5%), and 0.1 g (chitosan) caused the surface morphology of film C to become rough, have a cavity and fracture. The surface morphology of Film D (the amount of chitosan is twice that of ZnO/CuO nanoparticles) is different than film C and E. The surface morphology of film D was less homogeneous causing the high concentration of chitosan [56]. The amount of ZnO/CuO nanoparticles is twice that of chitosan at film E, the fracture surface is seen the film E (Figure 12c).…”
Section: Characterization Of Metal Oxide Nanoparticles and All Films ...mentioning
confidence: 99%
“…Figure 12a shows the synthesis of film C from the mixture of 0.1 g (ZnO/CuO nanoparticles), 10 mL (PVA 2.5%), and 0.1 g (chitosan) caused the surface morphology of film C to become rough, have a cavity and fracture. The surface morphology of Film D (the amount of chitosan is twice that of ZnO/CuO nanoparticles) is different than film C and E. The surface morphology of film D was less homogeneous causing the high concentration of chitosan [56]. The amount of ZnO/CuO nanoparticles is twice that of chitosan at film E, the fracture surface is seen the film E (Figure 12c).…”
Section: Characterization Of Metal Oxide Nanoparticles and All Films ...mentioning
confidence: 99%
“…The films' degradability was evaluated using a standard soil, following the ASTM G160-12 standard [15] . Film samples made using the optimal formulation were packed with inert net packaging to protect the samples against physical damage and help identify them in the soil.…”
Section: Degradability Testsmentioning
confidence: 99%
“…Mendes et al [60] , producing thermoplastic starch films containing pectin and lemongrass essential oil, observed that the produced films took 20 days to decompose when exposed to soil. Leonardelli et al [15] , evaluating the biodegradability of whey-based films by adding chitosan as an antimicrobial agent, reported a degradation time of 8 days for films when disposed of in soil. Film degradability was similar to those of other biopolymeric films and superior to commercial films, considering that plastic films have degradation times longer than one year, even when discarded in landfills [61] .…”
Section: Film Degradability Testsmentioning
confidence: 99%
See 1 more Smart Citation